DIPLOMAT TERMINOLOGY AS A LINGUISTIC OBJECT - Xumora Axmadjonova Murodjon qizi, Majidova Ra`no (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This scientific article is devoted to the study of diplomat terminology as a linguistic object. Lexicon related to the field of diplomacy is of great importance not only in the scientific, but also in the political and cultural context. The article considers the analysis of diplomatic terms from a linguistic point of view, the uniqueness and differences of diplomat terminology in English and Uzbek, as well as the role of these terms in international communication. The analysis of diplomatic terms as a linguistic object allows us to determine their semantic aspects, communicative functions and place in intercultural relations. The article may be useful for linguists, specialists working in the field of diplomacy, and language teachers.